2017
DOI: 10.3311/ppme.9114
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Cutting Parameters to Minimize the Surface Roughness in the End Milling Process Using the Taguchi Method

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 9 publications
1
24
0
Order By: Relevance
“…Through the mapping in the Taguchi method, the values of the repeated quality characteristics under the same conditions can be processed to find out the factors that can affect the variation. Using the signal-to-noise ratio (S/N), the value of the repetitive quality characteristics is integrated into the value for the size of reactive variation [12].…”
Section: Taguchi Methodsmentioning
confidence: 99%
“…Through the mapping in the Taguchi method, the values of the repeated quality characteristics under the same conditions can be processed to find out the factors that can affect the variation. Using the signal-to-noise ratio (S/N), the value of the repetitive quality characteristics is integrated into the value for the size of reactive variation [12].…”
Section: Taguchi Methodsmentioning
confidence: 99%
“…With the help of a Mathematical model, Burlacu et al [13] tried to minimize surface roughness in micro-milling of C45W steel. Using Taguchi L9 orthogonal array in end milling of hardened steel block, João et al [14] tried to find the control factor to optimize the surface roughness. They identified that Radial depth of cut is the most influencing factor in minimizing surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most commonly used techniques for the design of experiments (DOE), such as the factorial and response surface method (RSM), the Taguchi technique is considered to be very effective since it offers a quality and simplicity to have an optimized design with an optimum cost [19]. The Taguchi technique is used to find out the best factors amongst the total operating factors by avoiding the full factorial experiment runs [20].…”
Section: Design Of Experiments (Doe)mentioning
confidence: 99%